Morphogenesis and tissue flow in Tanzânia grass under different forage allowances - Marco Aurélio Alves de Freitas Barbosa; Fabiola Cristine de Almeida Rego; Valter Harry Bumbieris Junior; Vinicius Campachi Brito; Ulysses Cecato; Rafael Mantegazza Saad; Renan Lucas Miorin (Semina: Ciências Agrárias, 2014)
This study was conducted to identify effective strategies for grazing managing of Panicum maximum Jacq cv. Tanzãnia, under continuous stocking with variable stocking rate, based on assessments of their morphogenetic and structural characteristics. Four forage allowances: 3, 7, 11, and 15% BW were studied. A randomized block design, with three replicates was used, with split plot, where FA 4 as main plots and subplots were established cages. The number of basal tillers per cage protected and unprotected, both remaining as the new, decreased with FA. The unprotected tillers had higher numbers than cage protected. The weight of tillers and roots showed curvilinear response function in the FA. There was no effect of period at tillering (P> 0.05) of Tanzania grass. The total length of sheets, protected or not by exclusion cage and ligule height of tillers per cage had unprotected quadratic fit function OF. The ligule height protected tillers showed linear response function in the OF. The total number of leaves, expanded and expanding, tiller protected or not by exclusion cage, showed no differences between the FA and cage exclusion. The use of forage allowance of 11% of body weight for tanzania grass managed under continuous grazing and variable stocking rate, seems to be more sustainable